Kajian Mimetik dan Kepribadian Tokoh pada Novel “Keterasingan” Karya Priska Siagian Serta Implikasinya dalam Pembelajaran: Mimetic Study and Character Personality in the Novel “Keterasingan” by Priska Siagian and Its Implications in Learning - Girsang, Lisfa Agustin; Frince S, Monalisa; Gusar, Martua Reynhat Sitanggang (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the mimetic depiction and personality of the characters in the novel Keterasian by Priska Siagian and examine its implications for literature learning in high school. The approach used in this study is qualitative with a descriptive method. The main focus of this study lies in mimetic analysis, namely the depiction of the reality of life reflected in the novel, as well as the analysis of the character's personality based on Sigmund Freud's psychoanalytic theory, which includes three main personality structures: id, ego, and superego. The data collection technique used the reading and note-taking technique, where the researcher marked quotations relevant to the novel's object of study. The study results indicate that the novel Keterasian represents a social reality related to the alienation of individuals from the social and cultural environment. The mimetic depiction is seen in the setting, plot, and conflicts experienced by the main character. In addition, the personality of the main character in the novel can be analyzed through the dynamics between the id, ego, and superego, which influence each other in decision-making, and the character's attitude towards internal and social conflicts. The implications of the results of this study indicate that the novel Keterasingan can be used as teaching material in literature learning in high school, especially in introducing students to the intrinsic elements of literary works and psychological approaches to understanding character. This will improve students' critical and in-depth literary analysis and appreciation skills.